PERBAIKAN TEKNIK PENGOLAHAN KERANG KUPAS DI DESA PERCUT KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG - Muji Paramuji; Rahmad Setia Budi; M. Imam Fajar (Universitas Islam Sumatear Utara, 2023)
Some of the people of Percut village make a living as fishermen catching fish and collecting shells. The consumptive culture of coastal communities, especially seafood and beach products, provides opportunities to produce innovative culinary businesses. After conducting socialization and hearings with the Percut village community, information was obtained that a breakthrough effort had been made in the marketing of shelled clams. The shelled clams here are sourced from feather clams (Anadara antiquata), although there are several other types of shellfish such as green mussels, hemp clams and other shellfish. On the coast of Percut village it is quite easy to get clams and several other types of shellfish, but the processing is still very simple, namely by simply boiling them. This processed product still contains impurities (sand or mud), the appearance is less attractive, the type and size are not the same and the packaging is not attractive so that the attractiveness and interest of the public to buy is still very low. Therefore, technical improvements are needed from the beginning of the shellfish processing process in order to obtain quality results and be accepted by the market. It is hoped that the improvement in processing techniques for peeled shellfish in Percut village will provide added value from shellfish products and the establishment of a Percut village-specific culinary snack business that will increase people's interest in buying them.